Libros en Mano: Phonological Awareness Intervention in Children's Native Languages - Wendy Gonzales; Marie Tejero Hughes (MDPI AG, 2018)
The growing diversity in schools in the United States resulting from the rising number of English learners (ELs) has put more pressure on both children and teachers. Teachers are faced with the challenge of meeting the educational needs of culturally and linguistically diverse (CLD) learners, including the unique needs of CLD children with academic delays or disabilities. As early as preschool, many ELs are performing academically lower than their monolingual peers in literacy, and the gap can be even greater for ELs identified as having a delay or disability. However, providing explicit phonological awareness interventions in the child’s native language may help improve English reading outcomes and mediate the negative effects on reading achievement attributed to limited English proficiency. This intervention study looked at how a phonologically based emergent literacy intervention provided in Spanish to four EL preschoolers affected their emergent literacy and phonological awareness outcomes in English and Spanish. All of the children increased their overall emergent literacy and phonological awareness skills in both English and Spanish. The findings indicated that all four children showed some increase in English phonological awareness skills in both syllable segmentation and letter sound knowledge, while sound isolation and sound segmentation demonstrated mixed results across participants.